Vpliv telesne vadbe v nosečnosti na pojavnost poporodne depresije - Kante, Katarina (Obzornik zdravstvene nege, 2025)
ntroduction: New situations such as childbirth are physically and psychologically stressful, especially if accompanied by postnatal depression, the most common postnatal mental disorder with possible long-term effects. The aim of this integrative literature review is to examine the effects of exercise interventions during pregnancy on the development of postnatal depression and to determine whether all exercise interventions are equally efficient. Methods: A systematic search of two electronic databases was conducted and included studies of women who had undergone an exercise intervention during pregnancy. From the 451 identified hits, four randomised controlled studies published between 2015 and 2022 were included in the final analysis. This review was conducted and reported in line with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement, and the Mixed Methods Appraisal Tool (MMAT) was used to assess methodological quality.Results: Two of the four studies included in this review reported that exercise interventions reduce the development of postnatal depression. All studies claim that modern intervention approaches are needed.Discussion and conclusion: The results of this integrative literature review cannot fully confirm whether exercise intervention in pregnancy can effectively reduce the development of postnatal depression. The limitations of this review along with the scarcity of relevant studies call for further research in this field. Nevertheless, physical activity in pregnant women should be encouraged by physiotherapists and other health professionals.
Keywords: birth; depresija; depression; exercise intervention; fizioterapija; health education; physiotherapy; porod; vadbena intervencija; zdravstvena vzgoja